The Spanish Civil War : revolution and counterrevolution - Bolloten, Burnett (University of North Carolina Press, 2015)
Annotation This monumental book offers a comprehensive history and analysis of Republican political life during the Spanish Civil War. Completed by Burnett Bolloten just before his death in 1987 and first published in English in 1991, "The Spanish Civil War" is the culmination of fifty years of dedicated and painstaking research and is the most exhaustive study on the subject in any language. It has been regarded as the authoritative political history of the war and an indispensable encyclopedic guide to Republican affairs during the Spanish conflict. This new edition includes a new introduction by Spanish Civil War scholar George Esenwein, an updated bibliography featuring books on the Spanish Civil War published since 1987, and seventy-three photos of the war's participants
Keywords: Negrin, Juan.; Negrín, Juan.; Partido Comunista de España -- History.; Negrín, Juan; Partido Comunista de España; Communism -- Spain -- History.; Spain -- History -- Civil War, 1936-1939.; Spain -- Politics and government -- 1931-1939.; Espagne -- Histoire -- 1936-1939 (Guerre civile); Espagne -- Politique et gouvernement -- 1931-1939.; HISTORY -- Europe -- Spain & Portugal.; HISTORY -- Military -- Other.; Communism; Politics and government; Spain; 1931-1939; History